Integration of Factor Analysis and Fiqh Muamalah to Entrepreneurial Behavior - Andre Yuberta; Ganefri Ganefri; Ambiyar Ambiyar; Asmar Yulastri; Yuliana Yuliana; Fadhilla Fadhilla (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
The development of modern entrepreneurship often focuses on economic efficiency, while the ethical dimensions of sharia-based principles remain underexplored empirically. This study places this issue within the context of Islamic jurisprudence (fiqh muamalah), specifically the principles of buying and selling that emphasize justice, trustworthiness, and the prohibition of gharar, as the basis of Islamic business ethics. The purpose of this study is to integrate a multivariate factor analysis approach with the principles of Islamic jurisprudence (fiqh muamalah) to develop a model of ethical entrepreneurial behavior in the Islamic trade system. The methods used include a survey of Muslim business actors in the trade and small industry sectors, followed by exploratory factor analysis (EFA) to identify the latent structure of sharia values, as well as confirmatory factor analysis (CFA) and structural equation modeling (SEM) to test the causal relationship between compliance with muamalah, ethical orientation, and business sustainability. The results of the study indicate that the latent variables "transaction fairness" and "business trustworthiness" have a dominant contribution to the formation of ethical entrepreneurial behavior, while the factor "prohibition of gharar and usury" functions as a moral controller in business decision-making. The conclusion of this study explains in detail the integration of the principles of muamalah fiqh in multivariate factor analysis strengthening the theoretical validity of Islamic entrepreneurship and providing a quantitative basis where transaction justice r = 0.68; business trustworthiness r = 0.63; prohibition of gharar and usury r = 0.59; blessing orientation r = 0.74.